2020
DOI: 10.7717/peerj.9137
|View full text |Cite
|
Sign up to set email alerts
|

Creatinine is a biochemical marker for assessing how untrained people adapt to fitness training loads

Abstract: Background To study the peculiarities of changes in creatinine concentration in blood serum of untrained men during the prolonged usage of training loads different in volume and intensity, and to determine the value of this biochemical marker for the assessment of adaptive body changes during fitness training. Methods We examined 50 untrained men aged 18–20 years who had no contraindications for practicing fitness. Taking into account the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 19 publications
2
22
0
5
Order By: Relevance
“…We discovered that the nature of changes in creatinine in the blood serum of both group participants before and after training load of different intensity during 2 months of research, confirmed the results of experimental studies in power fitness ( Titova et al, 2018 ; Chernozub et al, 2020 ). At the same time, the increase in basal creatinine level, which indicates growing resources for creatine phosphokinase response on the background of increasing fat-free mass and decreasing body fat, confirm the research results of a number of scientists ( Clarkson et al, 2006 ; Papassotiriou & Nifli, 2018 ; Stajer, Vranes & Ostojic, 2020 ).…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…We discovered that the nature of changes in creatinine in the blood serum of both group participants before and after training load of different intensity during 2 months of research, confirmed the results of experimental studies in power fitness ( Titova et al, 2018 ; Chernozub et al, 2020 ). At the same time, the increase in basal creatinine level, which indicates growing resources for creatine phosphokinase response on the background of increasing fat-free mass and decreasing body fat, confirm the research results of a number of scientists ( Clarkson et al, 2006 ; Papassotiriou & Nifli, 2018 ; Stajer, Vranes & Ostojic, 2020 ).…”
Section: Discussionsupporting
confidence: 77%
“…In this study we obtained the results and the peculiarities of changes in the biochemical blood parameters during special training in MMA and determined the correlation between them, which allowed to establish a minimum set of criteria for assessing adaptation to different training load regimes. A similar direction of research concerning adaptive-compensatory body reactions to power loads of different intensity was conducted with the intention to optimize the training system of MMA athletes and in other sports ( James et al, 2016a ; James et al, 2016b ; Crewther, Obmiński & Cook, 2018 ; Chernozub et al, 2019 ; Chernozub et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Muscle strength augmentation is the result of changes in the muscle structure such as muscular hypertrophy [ 67 , 68 ], neural adaptations such as increased mobilization of motor units [ 67 , 69 , 70 ], and metabolic adaptations of anaerobic energy [ 71 73 ]. Resistance training was found to initiate all these three mechanisms [ 67 – 73 ].…”
Section: Discussionmentioning
confidence: 99%